Accommodation issue of nuclear power in China: Status quo, barriers and solutions. (November 2018) - Liu, Pingkuo; Chu, Penghao; Hou, Jianchao
Abstract: With the slowdown in economic growth and the oversupply of electric power, the nuclear power accommodation issue in China has become more and more serious since 2015. One purpose of promoting the accommodation capacity of nuclear power in China is to enable the power system to absorb a higher proportion of clean energy. This paper introduces the current situation of the nuclear power industry development and its accommodation capacity, discusses the policy environment from the aspects of development planning, supporting mechanism and policy tools, and further analyzes the barriers of the nuclear accommodation by using PEST model. The countermeasures for China's nuclear power development are proposed accordingly with respect to the strengths, the weaknesses, the opportunities and the threats. Through this research, the conclusions and policy recommendations are put forward to strengthen the accommodation capacity of nuclear power. Highlights: Nuclear power accommodation issue in China has become more and more serious. Policy environment of the nuclear power is discussed. Barriers of the nuclear accommodation are analyzed. Countermeasures for nuclear power curtailment are proposed.